Employee innovative behavior and workplace wellbeing: Leader support for innovation and coworker ostracism as mediators - Wang, Hui; Chen, Xueshuang; Wang, Hui; Xie, Mingxing (Frontiers in Psychology, 2022)
Most of previous studies are focused on the antecedents of employee innovative behavior, while the examination of the outcomes of employee innovative behavior is rarely. Especially, the relationship between employee innovative behavior and workplace well-being has been ignored. Based on social comparison theory and social exchange theory, this study introduced coworker ostracism and leader support for innovation as mediating variables to explore the “double-edged sword” effect of employee innovative behavior on workplace well-being. Data collected from 319 employees in Chinese companies are used for empirical analysis. Empirical results demonstrate that: (a) employee innovative behavior is directly and positively related to workplace well-being; (b) employee innovative behavior is indirectly and positively related to workplace well-being through leader support for innovation; and (c) a negative association between employee innovative behavior and workplace well-being via coworker ostracism is unsupported. The theoretical and practical implications are discussed.